Activation of Water on MnOx-Nanocluster-Modified Rutile (110) and Anatase (101) TiO2 and the Role of Cation Reduction - Rhatigan, Stephen; Nolan, Michael (Frontiers in Chemistry, 2019)
Surface modification of titania surfaces with dispersed metal oxide nanoclusters has the potential to enhance photocatalytic activity. These modifications can induce visible light absorption and suppress charge carrier recombination which are vital in improving the efficiency. We have studied heterostructures of Mn4O6 nanoclusters modifying the TiO2 rutile (110) and anatase (101) surfaces using density functional theory corrected for on-site Coulomb interactions (DFT + U). Such studies typically focus on the pristine surface, free of the point defects and surface hydroxyls present in real surfaces. In our study we have considered partial hydroxylation of the rutile and anatase surfaces and the role of cation reduction, via oxygen vacancy formation, and how this impacts on a variety of properties governing the photocatalytic performance such as nanocluster adsorption, light absorption, charge separation and reducibility. Our results indicate that the modifiers adsorb strongly at the surface and that modification extends light absorption into the visible range. MnOx-modified anatase can show an off-stoichiometric ground state through oxygen vacancy formation and cation reduction spontaneously and both modified rutile and anatase are highly reducible with moderate energy costs. Manganese ions are therefore present in a mixture of oxidation states. Photoexcited electrons and holes localize at cluster metal and oxygen sites, respectively. The interaction of water at the modified surfaces depends on the stoichiometry and spontaneous dissociation to surface bound hydroxyls is favoured in the presence of oxygen vacancies and reduced metal cations. Comparisons with bare TiO2 and other TiO2-based photocatalyst materials are presented throughout.